2019
DOI: 10.1021/acs.energyfuels.8b04523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Injection Pressure and Air–Fuel Ratio on the Self-Ignition Properties of 1-Butanol–Diesel Fuel Blends: Study Using a Constant-Volume Combustion Chamber

Abstract: One of the ways to reduce the negative impact of diesel engines on the natural environment is to reduce the smoke opacity and emissions of nitrogen oxides. For this purpose, suitably programmed fuel injection strategies and exhaust after-treatment systems can be used. Another way to reduce the toxicity of diesel exhaust is to use oxygenated fuels. This approach is particularly important, as it also allows a reduction of the use of fuels processed from crude oil. As a potential oxygen additive, 1-butanol can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 125 publications
0
7
0
1
Order By: Relevance
“…One of them is attributed to the ID, which may have effects on soot reduction for 1-butanol blends. Previous research work had conducted a systematically study on the ID of the 1-butanol blends, and the results indicated that ID increased linearly with the volume percentage of butanol in blends increasing. The longer ID implies that the butanol blends have more sufficient time to mix with the ambient air.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is attributed to the ID, which may have effects on soot reduction for 1-butanol blends. Previous research work had conducted a systematically study on the ID of the 1-butanol blends, and the results indicated that ID increased linearly with the volume percentage of butanol in blends increasing. The longer ID implies that the butanol blends have more sufficient time to mix with the ambient air.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The experimental results showed that CO, NO X , and smoke emissions declined while the unburned hydrocarbon (UBHC) emissions rose by adding butanol into the blends. Kuszewski et al 27 investigated the selfignition characteristic of 1-butanol/diesel blends with the change of volume fraction of 1-butanol in a CVCC. Zhang et al 28 examined the effects of addition of 1-butanol in blends on the characteristics of spray combustion and soot emissions in a CVCC designed to mimic a heavy-duty diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…As a renewable substance, 1-butanol has properties such as low volatility and good oil solubility . It can shorten the ignition delay time and is applied to improve the performance of EHFs. , …”
Section: Introductionmentioning
confidence: 99%
“…26 It can shorten the ignition delay time 27 and is applied to improve the performance of EHFs. 28,29 The thermophysical properties of a fuel have a vital influence on its capabilities, in which density and viscosity are the two most important indexes. 30 The density is directly related to the volumetric energy, which can affect propulsion energy for aircrafts with limited fuel tank volume.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, the fuels above are nearly undepleted raw material base -both mineral (natural gas, coal, oil shale) and organic (potato, beet, vegetable oils and their waste, algae, etc.) giving an advantage of using the above as raw material [2][3][4][5][6]. Availability of n-butanol production facilities makes the use of alcohols as additives in diesel fuels economically feasible.…”
Section: Introductionmentioning
confidence: 99%